Pengaruh Work Life Balance, Work Overload dan Burnout terhadap Kinerja Pegawai Dinas Kesehatan Kabupaten Kulon Progo - Triana Nurshoimah; Hari Nurweni; Retno Hartati (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
The purpose of this study is to determine the effect of work life balance, work overload and burnout on the performance of Kulon Progo District Health Office employees. The population is all employess with ASN and PPPK status, using a non-probability sampling technique using a saturated sample. The number of respondents was 75 people. Data collection was carried out using a questionnaire. Data analysis method with instrument test, basic assumption test, classical assumption test, and data analysis that consists of t test, f test, and multiple linear regression analysis. The results showed that work life balance has a positive effect on performance, work overload has no effect on performance and burnout has no effect on performance.